Ensino por investigação: contribuições de um curso de formação continuada para a prática de professores de ciências naturais e biologia - Oliveros, Paula Bergantin (2013)
Normally initial teacher training has not been sufficient to provide all the tools for an updated and efficient teaching practice. It is presented here one of the ways of working the completion of the initial training through a course of continuing education. This course is based on inquiry teaching which is considered an important teaching strategy for science education. This kind of teaching enables improvement of students reasoning and cognitive skills, the cooperation among them, the understanding of the nature of scientific work, and the motivation to think about the relationship between science, technology, society and environment. For this dissertation a course of continuing education based on this approach was followed in order to evaluate which contributions it can bring to the teaching practice. The course was followed based on three stages: on the first there was a questionnaire and an informal interview; next it happened through participant observation with audio and visual aid; the third stage happened through semi structured interview. The collected information was analyzed based on Content Analysis. An inquiry teaching pedagogical material was produced for the course including some examples and applications of this approach. The aim of the material is that it can be a support for the teachers after de course. The results allowed seeing that the course was very useful, different from the traditional and the teachers that put the approach to use found it to be very positive. Thus it can be said that some of the teachers who participated will try again to apply it, try to contextualize more the teaching situations with the students day to day life, as well make them more active and critic. We can also gather from the study, that the inquiry teaching is a very different tool from what the teacher was taught and is accustomed to use and the theoretical comprehension, acceptance and practice change is a complicated process and demands time